Using new morphological criteria to identify domesticated emmer wheat at the aceramic Neolithic site of Chogha Golan (Iran). (May 2015) - Weide, Alexander; Riehl, Simone; Zeidi, Mohsen; Conard, Nicholas J.
Abstract: Reconstructing the domestication process of cereals is a basic requirement for the understanding of the Early Neolithic in the Near East and how agriculture emerged. Although there is general agreement on the criteria of differentiating wild from domesticated cereals, their application to material from aceramic Neolithic sites is problematic for reasons of preservation and diversity of early transitional chaff remains. In the present study we established an identification key for the distinction of wild and domestic emmer wheat ( Triticum turgidum subsp. dicoccoides / dicoccum ). General morphological analyses as well as experimental charring and measurements on wild and domestic emmer from the Fertile Crescent were conducted to track the main features that distinguish the two forms. Wild emmer can be differentiated from domestic emmer using longitudinal sections through rachises. The scar morphology of wild emmer specimens with a rough upper abscission scar is distinct from domestic emmer. In addition, two of the measuring tracks distinguish between domestic emmer and its progenitor. These results were applied to archaeological specimens from the aceramic Neolithic site of Chogha Golan (Ilam Province, Iran), which was excavated in 2009 and 2010 by a team of the Tübingen Iranian Stone Age Research Project. The carbonized emmer remains dating to about 9800 BP comprise domestic-type and wild-type rachises, which is typical for cereal assemblages from aceramic Neolithic deposits. Highlights: Morphology of wild and domestic emmer wheat accessions was analyzed. Both are distinguishable using the upper abscission zone in longitudinal section. Rough scars among wild emmer are distinct from rough scars of domestic emmer. Domestic-type emmer dating to about 9800 B.P. was identified at Chogha Golan.